Teaching scientific literacy by the help of ICT - Vrana, Radovan (2012)
Science plays a very important role in education. It is a rich and infinite source of information and it influences and governs many decisions in our lives. To successfully understand scientific concepts and processes required in education and make proper decision in personal life, one must be scientifically literate. Scientific literacy is one of the basic forms of literacy in the digital age. It assumes possession of a capacity to understand and use scientific knowledge and to be informed member of the society who will be able to make decisions based on scientific facts. Scientific content necessary for teaching of scientific literacy is nowadays widely present and available, especially in digital format on the internet. The internet has become the fastest growing medium which provides ubiquitous access to scientific information resources by the help of several internet services such as wikies, blogs, portals, social networks etc. These internet services facilitate teaching of students and the public about scientific discoveries and help improving their scientific literacy. This paper provides an overview of the most important facts about scientific literacy and internet services that are used in teaching scientific literacy.
Projekt MZOS
ENG